POTENTIAL CANDIDATES FOR VILLAGE YOUTH LABOR IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 AND COVID'19 PANDEMIC (Study on Tanjung Medang Village Youth) - Randi, Randi; Mulyanto, Mulyanto; Taqwa, Ridhah; Junaidi, Junaidi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Industrial Revolution 4.0 and Pandemic Covid'19 is a new challenge for the world community, the condition of the physical and digital world undergoes a significant change in the way of human life, namely integrating the physical, digital and biological world, where there are fundamental changes and new breakthroughs in all disciplines, including artificiall intelligence, nanotechnology, biotechnology, internet-based technology impacting human life, impacting economic growth. (Hamdan, 2018). The 4.0 industrial revolution improved efficiency, flexibility and cross-border connectivity, as well as faster, cheaper, and more specific services. However, technology is also increasing access to digital disparities, competency gaps of social science graduates with industry needs. Employee recruitment will be reduced as automation, robotics use and flexible working systems increase. The limitations of mastering technology for the workforce in the village make it difficult for village youth to compete and get decent jobs. Both the private sector and the government should still prioritise the target of access to permanent employment for everyone because that is where human personal development (Vieronica Varbi Sununianti, 2019). The focus of this paper is on improving Human Resources through training. Keywords: Enhancement, Technology, Training, Internet, Youth